Case Report: Cholecystitis and gastric perforation caused by a fishbone and treated by laparoscopic surgery - Li, Xuemin; Cheng, Junfeng; Wang, Yonghang; Chen, Zhijun; Chen, Zewei; Ren, Chao (Frontiers in Medicine, 2025)
Rare cases of swallowed fish bones leading to cholecystitis and gastric perforation have been reported. Here, we present the case of a 71-year-old male patient who experienced 10 days of right upper quadrant pain after eating fish. Laparoscopic repair of gastric perforation and cholecystectomy was performed and successfully removed a fishbone of 3 cm in length from the region between the gallbladder cavity and the gastric antrum. The patient was 10 days after surgery and recovered well. No sign of recurrence was observed at the 3-month follow-up.